Nurse personal robot: An automated robust control nurse following robot with self leveling platform, special wheel, suspension system and sensor integration for crowded hospital ward - Azrul, Ahmad; Sulaiman, Bakri; Bukhari, Ilias; Abdul Hamid, Adom, Prof. Madya Dr.; Sazali, Yaacob, Prof. Dr.; Ramachandran, Nagarajan, Prof. Dr.; Khaled, Helmy, Dr.; Mohd. Khairul, Helmy; Muhammad Zairy, Shazni; Mohd Al Haffiz, Saad (Universiti Malaysia Perlis (UniMAP), 2012)
The 3rd International Engineering Invention & Innovation Exhibition 2012(i-ENVEX 2012) was organized by ENVEX Young Researcher Club (EYReC), University Malaysia Perlis (UniMAP) and Malaysia High Education Ministry at 2020 Hall, Kangar, Perlis, Malaysia.